Analisis Penerapan Corporate Social Responsibility Terhadap Profitabilitas pada CV. Tiara Abadi Pamekasan - Andrean Supriadi; Nur Diana; Hariri Hariri (Universitas Islam Malang, 2023)
This study aims to (1) determine the implementation of Corporate Social Responsibility (CSR) on the CV. Tiara Abadi (2) To determine the impact of implementing Corporate Social Responsibility (CSR) on the CV. Tiara Abadi to the profitability obtained. This research is a quantitative and quantitative descriptive type. Based on the statistical test of the minimum, maximum, and mean values, there is an increase after implementing Corporate Social Responsibility (CSR). Based on the analysis results, the effect of CSR implementation on the company's profitability is known (1) CV. In implementing CSR, Tiara Abadi is oriented to the balance of profit, people, and the planet by allocating funds of 1% of profits and allocated to environmental activities by 0.3% and social activities by 0.7%. (2) Profitability CV. It can be seen from the results of research that has been done that there are differences in profitability before and after implementing CSR.Keywords: Corporate Social Responsibility, balance of profit, quantitative descriptive